Nursing research : generating and assessing evidence for nursing practice - Polit, Denise F.; Beck, Cheryl Tatano (Philadelphia : Wolters Kluwer, 2021)
Research methodology is a dynamic enterprise. Even after writing 10 editions of this book, we have continued to draw new material and inspiration from ground-breaking advances in research methods and in nurse researchers' use of those methods. It is thrilling to share many of those developments in this new edition. We expect that many of the new methodologic and technological enhancements will be translated into powerful evidence for nursing practice. Four years ago, we considered the 10th edition as a watershed edition of a classic textbook, having added two new chapters. We are persuaded, however, that this 11th edition is even better than the previous one. We have retained many features that made this book a classic textbook and resource, including its focus on research as a support for evidence-based nursing, but have introduced important innovations that we hope will help to shape the future of nursing research"-- |c Provided by publisher.
Includes bibliographical references and index.
Keywords: Nursing research -- Methods